2002
DOI: 10.1038/sj.cdd.4400937
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of ATP favours apoptosis over necrosis triggered by benzamide riboside

Abstract: A new synthetic drug, benzamide riboside (BR) exhibited strong oncolytic activity against leukemic cells in the 5 ± 10 mM range. Higher BR-concentrations (20 mM) predominantly induced necrosis which correlated with DNA strand breaks and subsequent depletion of ATP-and dATP levels. Replenishment of the ATP pool by addition of adenosine prevented necrosis and favoured apoptosis. This effect was not a pecularity of BR-treatment, but was reproduced with high concentrations of all trans-retinoic acid (120 mM) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Apoptosis is an energy-requiring process (45)(46)(47)(48)(49). Indeed, the presence or absence of ATP has a profound effect on whether the cell will die by apoptosis or necrosis (48).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is an energy-requiring process (45)(46)(47)(48)(49). Indeed, the presence or absence of ATP has a profound effect on whether the cell will die by apoptosis or necrosis (48).…”
Section: Discussionmentioning
confidence: 99%
“…Any modification of the structure of AAI, namely the addition, deletion, substitution, or replacement of these side chains drastically reduces toxicity. In AAII, the removal of the ''methoxy'' group from its position reduces the toxicity of AAII, a compound that differs from AAI by one ''methoxy'' group [17]. Therefore, specificity of AA and its activity are dependent on the chemical structure and conformation of particular AA specie as well as on the intracellular environment in specific tissue.…”
Section: Discussionmentioning
confidence: 98%
“…The morphological criteria defining the cell death type upon staining were as follows: the nuclei of viable cells stain blue (the cytoplasm remains invisible); apoptotic cells can be recognized by condensed chromatin, which usually stained more intensely blue; a similar chromatin condensation is observed at the late stage of apoptosis, but the color shifts to pink due to PI intrusion through leaky membranes; pink colored nuclei without chromatin condensation are typical of necrotic cells [17]. Using this approach, we found that most of the nonapoptotic dead cells were necrotic.…”
Section: Aai Inhibits Gdh Activity In Proximal Tubule Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of intracellular energy supply has been shown to switch apoptosis to necrosis [14]. Conversely, maintenance of the energy supply favors cell death by apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%